Appraisal of Teachers’ Comments on Primary Students’ Reports: A Systemic Functional Linguistics - Sihombing, Indah Andriyani; Sinar, Silvana; Zein, Thyrhaya (Journal of Languages and Language Teaching, 2025)
This study investigates how teachers employ appraisal attitude resources—specifically affect, judgment, and appreciation—in their written comments on primary students' report cards, using the analytical lens of Systemic Functional Linguistics (SFL). Drawing on a qualitative phenomenological case study design, the research analyzed 30 teacher comments drawn from three subject areas: Mathematics, Language Arts, and Mandarin. The data collection also involved unstructured interviews with teachers to gain deeper insight into their comment-writing practices and underlying intentions. The analysis revealed a marked dominance of judgment resources, with 69 instances noted, which primarily conveyed evaluations of students' capabilities, behaviors, and attitudes toward learning. This was followed by 32 instances of appreciation, used to recognize the quality of students' work or learning outcomes. The least frequent were affect resources, with only 15 instances, indicating that emotional engagement or references to students' feelings were not a central focus in most comments. This distribution underscores a pedagogical emphasis on assessing students through their actions and academic performances rather than their emotional experiences. The study concludes by emphasizing the need for greater awareness of the linguistic resources teachers use in feedback and suggests that professional development in appraisal language could help teachers craft more holistic, meaningful, and student-centered evaluations.